2018
DOI: 10.1145/3180494
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Geodesic Nets for Modeling Developable Surfaces

Abstract: We present a discrete theory for modeling developable surfaces as quadrilateral meshes satisfying simple angle constraints. The basis of our model is a lesser known characterization of developable surfaces as manifolds that can be parameterized through orthogonal geodesics. Our model is simple, local, and, unlike previous works, it does not directly encode the surface rulings. This allows us to model continuous deformations of discrete developable surfaces independently of their decomposition into torsal and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 33 publications
(45 reference statements)
0
89
0
Order By: Relevance
“…Note, however, that this increases the number of free variables substantially. In Figure 9, we show different time-discrete geodesics in NRIC where we use the quadratic deformation energy (15) in (23). In particular, we compare for end shapes being two oppositely bent plates our NRIC geodesic (orange) to the linear interpolation (green) in the embedding space R 2|E| , which corresponds to a naive transfer of the projection approach by Fröhlich and Botsch [2].…”
Section: Numerical Experiments and Comparisonsmentioning
confidence: 99%
“…Note, however, that this increases the number of free variables substantially. In Figure 9, we show different time-discrete geodesics in NRIC where we use the quadratic deformation energy (15) in (23). In particular, we compare for end shapes being two oppositely bent plates our NRIC geodesic (orange) to the linear interpolation (green) in the embedding space R 2|E| , which corresponds to a naive transfer of the projection approach by Fröhlich and Botsch [2].…”
Section: Numerical Experiments and Comparisonsmentioning
confidence: 99%
“…Our work is based on modeling a developable surface as a discrete orthogonal geodesic net (DOG) [Rabinovich et al 2018a], a model that has been shown both theoretically and empirically to avoid extrinsic and intrinsic deformation locking. We further rely on [Rabinovich et al 2018b] to explore the shape space of DOGs, but we replace their Laplacian ow based deformation with a sequential quadratic programming (SQP) based algorithm, detailed in Sec.…”
Section: Related Work 21 Modeling Developable Surfacesmentioning
confidence: 99%
“…5 for an illustration. Following [Rabinovich et al 2018a] we maintain continuity of curve points along edges while penalizing deviation of the edge lengths across duplicated quads.…”
Section: Modelmentioning
confidence: 99%
“…1.1.2 Geometric Modeling Approaches. Geometric modeling techniques have been widely developed for computing flat panels that can be assembled into a given 3D shape -e.g., segmentation-based methods [Julius et al 2005;Shatz et al 2006;Wang 2008], strip-based methods [Mitani and Suzuki 2004;Schüller et al 2018]), methods based on developable surfaces [Kilian et al 2008;Liu et al 2006;Rabinovich et al 2018;Rose et al 2007] and structures for selfdeformation [Guseinov et al 2017]. However, they cannot be directly used in the computation of fabric formwork as the shape of a fabric container will be deformed significantly after pouring in the liquid plaster.…”
Section: Related Workmentioning
confidence: 99%